Comparative Analysis of the SMARTER and ELECTRE Methods for Determining Priority Recipients of Free Legal Aid - Susi Widyastuti; Wahyu Ariandi; Muhammad Erwanto; Wilda Adela Pusriyanto (MASI Mandiri Edukasi, 2026)
Access to justice is a fundamental right guaranteed to every citizen by the Constitution. One implementation is the prodeo service, which covers court fees for those with financial difficulties. However, the implementation of prodeo services at the Cirebon City Religious Court still faces challenges in determining recipient priority due to the lack of a multi-criteria decision-making mechanism capable of objectively and measurably assessing various aspects. This study aims to provide recommendations for methods that can assist the court in determining the priority of prodeo service recipients in a transparent, fast, and targeted manner. The methods used are Multi-Criteria Decision Making (MCDM), namely SMARTER (Simple Multi-Attribute Rating Technique Exploiting Ranks) and ELECTRE (Elimination Et Choix Traduisant la Realite). The study was conducted using a quantitative, descriptive-comparative approach, based on Prodeo application data that includes criteria such as income level, number of dependents, health conditions, and case urgency. The results showed that both methods produced objective, transparent priority rankings of prodeo recipients, but differed in computational complexity and efficiency. The SMARTER method had advantages in simplicity and processing speed, while the ELECTRE method excelled at considering dominance among alternatives with high accuracy.